2013
DOI: 10.1503/cjs.028411
|View full text |Cite
|
Sign up to set email alerts
|

Transanal endoscopic microsurgery: impact on fecal incontinence and quality of life

Abstract: Background: Anal dilation during tumour excision with transanal endoscopic microsurgery (TEM) has caused concerns regarding postoperative anal function. We sought to determine whether TEM affects anorectal function and quality of life. Results: Forty patients received TEM; 30 of them met all inclusion criteria and agreed to participate. The median age was 70 (42-93) years, and median follow-up time between the interview and the operation was 365 (55-712) days. Tumours excised included 19 adenomas, 8 carcinomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 24 publications
2
11
1
3
Order By: Relevance
“…Previous studies have demonstrated that morbidity rates after CRT and local excision are not insignificant. For these reasons, it seems inappropriate to compare the present study with previous studies that included patients with benign disease or early‐stage (pT1–2) rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that morbidity rates after CRT and local excision are not insignificant. For these reasons, it seems inappropriate to compare the present study with previous studies that included patients with benign disease or early‐stage (pT1–2) rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have investigated the impact of local excision for rectal neoplasms on bowel and sexual function and on QoL, most of these studies had small sample sizes, were retrospective, comprised single‐institution experiences, included patients with benign lesions, and did not use validated questionnaires to assess functional results and QoL.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 however, no clinically significant postoperative fecal incontinence has been reported. 5,6 transanal minimally invasive surgery (tamis) is a relatively new technique using a disposable flexible port in combination with conventional laparoscopic instruments for local excision of rectal polyps. 7,8 the startup costs for this method are less compared with that of the tem equipment, although there are ongoing costs per case for flexible ports.…”
mentioning
confidence: 99%
“…No anastomosis was performed in this study, as the major end‐point of the study was to assess the feasibility of robotic transanal proctectomy. Although evaluation of postoperative anal continence is not possible in this model, as the size of the proctoscope in contact with the patient is the same as that in the TEM platform, no incontinence is expected .…”
Section: Discussionmentioning
confidence: 99%